prognostic factors in severe head trauma patients - الحمود, ياسر; محمد صالح علي; مفيد محفوض (Latakia University Journal -Medical Sciences Series, 2024)
Results: A total of 200 patients, 40 females (20%) and 160 (80%) males participated in the study, average age was 42 ±23 and average Glascow scale was 6±2, 123 (61.5%) patients deceased during the study. We studied the factors to discharge patients or to cause death. Sex and age do not factor, patients with higher Glascow scale had and patients with higher oxygen pressure were more likely to survive. Pupillary unresponsiveness and hypertension also affect the incidence of death post head trauma. We studied prognostic factors among discharged patients; we found that a good prognostic factor is associated with lower age, pupillary responsiveness and a normal partial pressure of oxygen.A good prognostic factor is not associated with cisterna effacement. Findings of CT-scan except for epidural hemorrhage, previous surgeries, sex and blood pressure are not associated with a prognostic factor.